Campbell's operative orthopaedics - Canale, S. Terry; Mosby-Year Book (St. Louis : Mosby, 1999)
(Producer) Contains the full text and the 7,900 illustrations from Campbell's operative orthopaedics, 8th ed. Details virtually every facet of surgical procedures step-by-step. Contains more than 2,300 new or redrawn illustrations; a new section on the foot; 11 new chapters on the wrist; completely revised chapters on general principles of infections, spinal infections, hip arthroplasty, and peripheral nerve injuries; alternative techniques for treating specific problems; and a review of malignant and benign bone tumors. Also contains five editions of the Year book of orthopedics, and Orthopedic boards review and Orthopedic boards review II.
CD is available at Koleksi Media Perpustakaan HUKM
System requirements: Macintosh; 4 MB RAM (8 MB recommended), hard disk drive with at least 8.1 MB free; Operating System 6.0.7 or later; CD-ROM installed with driver software.
System requirements: IBM 386/33 (or higher) or equivalent PC (486 recommended); 4 MB RAM (8 MB recommended), hard disk drive with at least 8.1 MB free; Windows 3.1 or higher; SVGA graphics monitor; mouse; CD-ROM installed with driver software.
Keywords: Orthopaedics -- CD-ROM